Directions of development of appraisal activity in Ukraine in accordance with modern challenges and world trends - Palekha, Yu.; Dekhtyarenko, Yu.; Tarnopolskyi, А.; Malashevskyi, М. (Land Management, Cadastre and Land Monitoring, 2022)
The theoretical and practical provisions of the methodology for evaluating land plots and real estate in Ukraine are summarized. Problematic aspects of assessment activities in modern conditions are revealed in view of the regulatory and legislative framework. The advantages of the transition to land plot assessment along with improvements in the quality of the tax base are substantiated. An analysis of methodological and methodical approaches to taxation of land plots and real estate existing in the world tax systems was carried out. The main groups of real estate taxation systems and land plots in its composition according to the method of establishing the tax base are defined. The possibility of using a new methodology for evaluating land plots and real estate is substantiated. The results of the study can regulate professional appraisal activities, eliminate shortcomings and gaps in the establishment and functioning of the appraisal institute in the land market.Keywords: monetary assessment; assessment of secondary rights; method; land plot; real estate; rental income; retrospective assessment; land fee; evaluation activity.